2015
DOI: 10.3389/fenvs.2015.00064
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and antibiotic resistance at beaches of the Galápagos Islands

Abstract: Tourism and residential population growth are increasing on the Galápagos Islands, yet the effects of this growth on environmental quality are not well understood. The goal of this study was to characterize recreational water quality on one of the inhabited islands of the Galápagos (Isla San Cristóbal). Five beaches were sampled to allow a comparison between beaches with and without discharge of human sewage, and to help elucidate the effects of human activities in this unique environment. Enterococcus concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…It has been reported that antibiotic resistant bacteria can equally be transmitted to humans during recreational use of fresh or marine water, which are natural aquatic habitats [ 246 ]. The natural aquatic environment, e.g., the surface waters, such as rivers and sea, serve as a receiving body of runoff water from farmlands fertilized with sewage sludge and animal manure, and wastewater discharged from treatment plants, which contain obvious concentrations of antibiotic resistant bacteria and their resistance determinants, along with biologically active metabolites of antibiotics or the parent compounds [ 247 ]. This causes great environmental damage and eutrophication, which might result in serious degradation of the water quality owing to the influx of high nutrients [ 248 ].…”
Section: The Great Challenge: Antibiotics Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that antibiotic resistant bacteria can equally be transmitted to humans during recreational use of fresh or marine water, which are natural aquatic habitats [ 246 ]. The natural aquatic environment, e.g., the surface waters, such as rivers and sea, serve as a receiving body of runoff water from farmlands fertilized with sewage sludge and animal manure, and wastewater discharged from treatment plants, which contain obvious concentrations of antibiotic resistant bacteria and their resistance determinants, along with biologically active metabolites of antibiotics or the parent compounds [ 247 ]. This causes great environmental damage and eutrophication, which might result in serious degradation of the water quality owing to the influx of high nutrients [ 248 ].…”
Section: The Great Challenge: Antibiotics Resistancementioning
confidence: 99%
“…The concentration/magnitude of these resistant bacteria in the recreational waters is determined by the local landscape (e.g., coastal waters), wind speed, ultraviolet radiation, temperature, rainfall, and the source and level of pollution [ 253 ]. In a study conducted by Overbey and colleagues [ 247 ], higher levels of E. coli and Enterococcus were enumerated in recreational water samples collected from sewage-impacted sites in five beaches in Galápagos Island, Ecuador. In addition, Fernandes Cardoso de Oliveira et al [ 254 ] revealed a higher level of multiple antibiotic resistance in heterotrophic marine bacteria recovered from sea water and sand in Gonzaguinha, the most organic polluted recreational beach, amongst Ilha Porchat and Guaraú beaches located in Southeast Brazil.…”
Section: The Great Challenge: Antibiotics Resistancementioning
confidence: 99%
“…Thus, the environmental and dietary exposure alone may have caused the transport of AMR across continents77. A study assessing the quality of recreational waters in Galapagos islands has found AMR genes in the water samples, and their close association with humans illustrates the dire consequences of such findings81. Thus, apart from the microbial interactions in the gut, various extraneous factors also affect our resistome.…”
Section: Factors Affecting the Human Gut Resistomementioning
confidence: 99%
“…Bacterial pathogens, include but are not limited to, those in the Enterobacteriaceae family (e.g., pathogenic E. coli, Klebsiella spp., Salmonella spp., Shigella spp., and Yersinia pestis) and Staphylococcus aureus (specifically MRSA), which have all been detected in ambient waters [15,[18][19][20]. Overall, the presence of AMR bacteria and ARGs in surface water is well established [15][16][17][18][21][22][23][24][25][26][27][28][29][30][31]. However, direct comparisons between these studies are difficult as the geography, AMR bacteria and ARGs selected for evaluation, sources of fecal impacts, and methods of determining resistance are highly variable between studies [27,32].…”
Section: Introductionmentioning
confidence: 99%